2014
DOI: 10.1161/circheartfailure.113.000952
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-23 and Cardiovascular Disease in the General Population

Abstract: Background Fibroblast growth factor-23 (FGF-23) is a phosphate regulatory hormone that directly stimulates left ventricular hypertrophy in experimental models. The role of FGF-23 in cardiovascular disease development in the general population is unclear. We tested associations of FGF-23 with major subclinical and clinical cardiovascular disease outcomes in a large prospective cohort. Methods and Results We evaluated 6,547 participants from the Multi-Ethnic Study of Atherosclerosis (MESA) who were initially f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
135
4
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 33 publications
4
135
4
2
Order By: Relevance
“…Specific associations have been reported for incident hypertension, LVH, incident HF, higher coronary calcium scores, and incident coronary heart disease 17, 19, 27, 28. In this study we confirmed previous findings reported by Kestenbaum et al linking serum FGF‐23 to incident HF, and further studied the association with subtypes of HFpEF and HFrEF.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Specific associations have been reported for incident hypertension, LVH, incident HF, higher coronary calcium scores, and incident coronary heart disease 17, 19, 27, 28. In this study we confirmed previous findings reported by Kestenbaum et al linking serum FGF‐23 to incident HF, and further studied the association with subtypes of HFpEF and HFrEF.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Seliger et al demonstrated that LVH was associated with higher risk of both types of HF, but especially HFrEF in older adults without prior HF or myocardial infarction in the Cardiovascular Health Study 41. Our findings of a strong association between higher FGF‐23 and higher risk of HFpEF cannot be explained fully by previous observations of the association between FGF‐23 and LV mass 18, 19. In sensitivity analyses we found that the association of FGF‐23 and HF remained significant even after adjusting for LV mass, suggesting that other pathological mechanisms could be mediating the association between FGF‐23 and the development of HF as mentioned in previous paragraphs.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…FGF23 is not only involved in the pathogenesis of CVD but also a marker of higher risk of CHF. [10,11,15] It has been shown that FGF23 concentrations are elevated in patients who are on dialysis; [10][11][12] , however whether there is an association between FGF23 levels and LVH and other echocardiographic indexes of LV dysfunction in patients who are on dialysis is still unproven. [13,14,16] Therefore, in this study, we decided to evaluate the role of FGF23 on LVH, left ventricular mass index (LVMI), and other echocardiographic findings in a group of patients on hemodialysis without known CVD.…”
Section: Introductionmentioning
confidence: 99%